Arthroscopic Rotator Cuff Restoration Using Sironix Suture Anchor: A Retrospective Observational Study - Krunal Shah; Ruchita Manwani; Ashok Kumar Moharana; Sachin Angrish; T. S. Deepak (Journal of Orthopedics, Traumatology and Rehabilitation)
Purpose: The most effective approach to treat individuals with rotator cuff tears (RCTs) remains uncertain, but operative treatment, especially arthroscopic surgery with various suture anchors, is becoming more popular. The purpose of this study was to assess the functional outcomes in patients who underwent arthroscopic RCTs restoration using Sironix suture anchors. Materials and Methods: Eighty patients (36 males and 44 females) who had arthroscopic rotator cuff restoration using Sironix suture anchors were included. Postoperatively, patients were followed up and functional outcomes were evaluated using the American Shoulder and Elbow Surgeons Standardization Shoulder Assessment (ASES), level of activity using the Simple Shoulder Test (SST) questionnaire, Quality of life using the Shoulder Pain and Disability Index (SPADI) scale, and Single Assessment Numerical Evaluation (SANE) score on a scale of 0–100. Adverse events were recorded post-RCTs restoration. Results: The functional outcomes were presented as the mean (standard deviation [SD]) values of total ASES, SPADI, and SST scores, which were observed to be 92.6 (05.28), 01.6 (02.46), and 90.3 (14.22), respectively. The SANE mean (SD) values of the operated shoulder and the opposite shoulder were 91.8 (10.22) and 97.3 (5.68), respectively, with a P = 0.0001. No serious adverse events were reported and none of the subjects discontinued the study. Conclusions: The current study demonstrated that the functional outcomes were quite satisfactory, with good results. Therefore, Sironix shoulder implants (CEPTRE® Knotted UHMWPE Suture PEEK Anchor and CEPTRE® Knotted UHMWPE Suture Titanium Anchor) were considered safe and effective in rotator cuff restoration.